Automated office blood pressure – being alone and not location is what matters most. Issue 4 (August 2015) - Armstrong, David; Matangi, Murray; Brouillard, Daniel; Myers, Martin G.
Abstract : Objective: Measurement of office blood pressure using a fully automated sphygmomanometer that takes multiple readings with the patient resting quietly alone has been called automated office blood pressure (AOBP). Almost all AOBP research has involved the patient resting alone in an examining room, which is often impractical in a clinical setting. The possibility that valid AOBP readings can be obtained with the patient resting quietly in a waiting room was examined. Methods: AOBP readings using the BpTRU device recorded with the patient resting quietly in the waiting room were obtained in patients referred for ambulatory BP monitoring. The relationship between the AOBP and the awake ambulatory blood pressure (AABP) (mmHg) was examined. Results: In 422 patients, the mean (±SD) AABP (139.4±13.4/80.7±10.6) was similar to the mean AOBP recorded in the waiting room (140.5±19.8/83.1±11.2), with both values being significantly lower than a single office BP (155.1±18.7/90.2±12.7) taken by a nurse. In the 178 untreated patients, the mean systolic AOBP and AABP were almost identical, with the diastolic AOBP being 1.5 mmHg higher. Bland–Altman plots for systolic BP showed a relatively consistent relationship for AOBP versus the AABP over the range of BPs recorded. The sensitivity, specificity, and accuracy for AOBP versus AABP were comparable with the values obtained with AOBP recorded previously in an examining room. Conclusion: AOBP readings recorded in a waiting room are comparable with the AABP, making it possible to obtain AOBP in clinical practice without the need to occupy an examining room.